ANTIMICROBIAL AND PHYTOTOXIC EFFECTS OF THE PLANT HELIOTROPIUM DASYCARPUM L. - M. ABUZAR GHAFFARI; S. BANO; K.HAYAT (International Journal of Pharma and Bio Sciences, 2013)
Heliotropium dasycarpum is an important desert plant of Boraginaceae family. The fresh extract of plant is used for the treatment of eye diseases. In the present study, dichloromethane and methanol crude extracts of plant was screened for antifungal, antibacterial and phytotoxic bioassay. Both extracts of Heliotropium dasycarpum inhibited the growth of Lemna minor L. and showed significant phytotoxic activities. The plantexhibited non-significant activity when tested against pathogenic gram positive and gram negative bacteria. The methanol extract of the plant showed 25% inhibition against a fungus, Microsporum canis. The phytochemical tests indicated the presence of alkaloids and cardiac glycosides in the plant.